Second Multicenter, Randomized, Double-blind, Parallel-group Evaluation of Effectiveness and Safety of Intravesical Sodium Chondroitin Sulfate Compared With Inactive Vehicle Control in Subjects With Interstitial Cystitis/Bladder Pain Syndrome - Nickel, J. Curtis; Hanno, Philip; Kumar, Keshava; Thomas, Heather (Urology (Ridgewood, N.J.), 2012)
To gain additional safety and effectiveness information regarding intravesical 2% chondroitin sulfate in subjects with interstitial cystitis/bladder pain syndrome (IC/BPS) in a controlled clinical trial. Women with IC/BPS were randomized to receive either 8 weekly bladder instillations of 20 mL of 2% chondroitin sulfate or 20 mL of inactive control solution. The primary effectiveness endpoint was the number of positive results using the Global Response Assessment at week 11 (4 weeks after the last instillation). The secondary effectiveness endpoint was a positive response to the Interstitial Cystitis Symptom Index (ICSI) at week 11. Additional effectiveness endpoints were changes from baseline at week 11 in the total ICSI score voiding diary, and visual analog scale for pain. A total of 98 eligible women with a diagnosis of IC/BPS met the inclusion criteria and were the intention to treat population. Of the 98 women, 83% completed the study. More patients in the chondroitin sulfate group (38.0%) reported moderate or marked improvement (considered responders) compared with the inactive control group (31.3%) at the 11-week endpoint visit. Similarly, more subjects in the active treatment group were classified as ICSI and VAS pain responders and reported a greater decrease in ICSI and VAS pain scores than the control group. None of these differences were statistically significant. Intravesical chondroitin sulfate therapy for IC/BPS might result in minor improvements in IC/BPS-related symptom and pain. However, the magnitude of benefit in our small pilot study does not support its use as monotherapy for this condition. Better strategies for selecting patients with a bladder-specific clinical phenotype might improve the overall response to this type of intravesical therapy.